The Effect of Profitability, Leverage and Dividend Payout Ratio on Profit Smoothing in Manufacturing Companies Listed on the IDX for the 2018 – 2020 Period - Weny Nurwendari; Rini Herliani; Ulfa Nurhayani (Outline Publisher, 2022)
Income smoothing is an action that is deliberately carried out by management to regulate the profits presented in the financial statements in accordance with the normal level of profit desired by the company's management. The purpose of this study was to determine the effect of Profitability, Leverage and Dividend Payout Ratio on Income Smoothing in Manufacturing Companies Listed in Indonesia Stock Exchange for year 2018-2020. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2020 as many as 193 companies. Based on the results of this study indicate that profitability partially has a significant negative effect on income smoothing, it can be proven that the significant value is 0.001 <0.05. Leverage partially has no effect on income smoothing, it can be proven that the significant value is 0.113 > 0.05. Dividend payout ratio partially has a significant negative effect on income smoothing, it can be proven that the significant value is 0.009 <0.05. Profitability, leverage and dividend payout ratio simultaneously affect income smoothing. It can be proven that the calculated F value is 5.181 and the f table value is 2.83, where the calculated f value is greater than the f table value, namely 5.181 > 2.83 with a significance value of 0.004 <0.05.